If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6 + x + 3 + x + 9 + x + 1 + x + 1 + x + 4 + x + 4 = 0 Reorder the terms: 6 + 3 + 9 + 1 + 1 + 4 + 4 + x + x + x + x + x + x + x = 0 Combine like terms: 6 + 3 = 9 9 + 9 + 1 + 1 + 4 + 4 + x + x + x + x + x + x + x = 0 Combine like terms: 9 + 9 = 18 18 + 1 + 1 + 4 + 4 + x + x + x + x + x + x + x = 0 Combine like terms: 18 + 1 = 19 19 + 1 + 4 + 4 + x + x + x + x + x + x + x = 0 Combine like terms: 19 + 1 = 20 20 + 4 + 4 + x + x + x + x + x + x + x = 0 Combine like terms: 20 + 4 = 24 24 + 4 + x + x + x + x + x + x + x = 0 Combine like terms: 24 + 4 = 28 28 + x + x + x + x + x + x + x = 0 Combine like terms: x + x = 2x 28 + 2x + x + x + x + x + x = 0 Combine like terms: 2x + x = 3x 28 + 3x + x + x + x + x = 0 Combine like terms: 3x + x = 4x 28 + 4x + x + x + x = 0 Combine like terms: 4x + x = 5x 28 + 5x + x + x = 0 Combine like terms: 5x + x = 6x 28 + 6x + x = 0 Combine like terms: 6x + x = 7x 28 + 7x = 0 Solving 28 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 7x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + 7x = 0 + -28 7x = 0 + -28 Combine like terms: 0 + -28 = -28 7x = -28 Divide each side by '7'. x = -4 Simplifying x = -4
| 0.5x-3=0.3(2x-3) | | -4.7k=10.81 | | x(13)=104 | | x(5)=55 | | 7t-2(-3t+1)=-3(1-3t) | | 8m-10=62+2m | | -11x+9=185 | | x+2(2)=0 | | 6d+5=-4-3d | | X+(x-355)+(2x+80)=2425 | | 3(-2y)+y=-10 | | 18-x=1 | | y=-16-16 | | -2(3y+4)=20 | | -1/3+1= | | 8y-2y+13=2y+12 | | 5w^2-6w+17=8 | | 6x^3-77x^2+56x+8=0 | | 48y-4(6-y)=12(3y+2) | | -3x-14=1 | | fu=3 | | -7(x+8)=35 | | 175x^2-28=0 | | 3a+9b-12= | | 4x+19=7-2x | | -5+4a+3a+6=0 | | 2x-8y=-34 | | -3(x-4)+10=-2 | | -49+9=-5 | | (7x+2)(3x-y)= | | 6(x+4)=3(4-2) | | x(7)=49 |